2020
DOI: 10.1186/s12957-020-01913-9
|View full text |Cite
|
Sign up to set email alerts
|

Natural disease progression and novel survival prediction model for hepatocellular carcinoma with spinal metastases: a 10-year single-center study

Abstract: Background: Individual prediction of life expectancy in patients with spinal metastases from hepatocellular carcinoma (HCC) is key for optimal treatment selection, especially when identifying potential candidates for surgery. Most reported prognostic tools provide categorical predictions, and only a few include HCC-related factors. This study aimed to investigate the natural progression of the disease and develop a prognostic tool that is capable of providing individualized predictions. Methods: Patients with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In our data, which were obtained from a tertiary care hospital, only 14.7% were given HCC-specific treatment. Only 3% underwent surgical intervention, which was even lower than the figure reported in the nearby University hospital (7%) [43]. In this situation, where most patients have incurable disease with progressive symptoms, integration of palliative care with standard oncologic treatment is appealing.…”
Section: Discussionmentioning
confidence: 72%
“…In our data, which were obtained from a tertiary care hospital, only 14.7% were given HCC-specific treatment. Only 3% underwent surgical intervention, which was even lower than the figure reported in the nearby University hospital (7%) [43]. In this situation, where most patients have incurable disease with progressive symptoms, integration of palliative care with standard oncologic treatment is appealing.…”
Section: Discussionmentioning
confidence: 72%
“…Spinal metastases starting from hepatocarcinomas are rare, with articles published to date reporting an incidence varying between 0.2% and 6% [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This type of metastases can be located in any of the regions of the spine, as follows: one-third is located in combined regions of the spine, another third in the thoracic region, a quarter of cases in the lumbar region, and less than 10% are identified in the cervical region [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another single-center study analyzed 1,143 patients with HCC and 69 of all (6%) had bone metastases. They concluded that an average ST in patients with bone metastases was 79 days and that four predictors of prognosis exist: age >60 years, poor Karnofsky Performance Status (vs. good and moderate), serum total bilirubin >3.0 mg/dL, and multifocality of HCC (vs. single tumor) [ 4 ]. In the other analysis, patients who have failed downstaging of metastatic HCC can achieve better prognosis than those without neoadjuvant therapy (median overall survival: 10.3 months vs. 4.0 months) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%